Seducing the subconscious the psychology of emotional influence in advertising - Heath, Robert 1947- (Chichester, West Sussex Wiley-Blackwell, 2012)
"Seducing the Subconscious reveals how this brave new advertising world works, using illustrative examples of advertising campaigns that have been hugely successful without anyone quite being able to recall what they were trying to communicate"-- Provided by publisher.
Keywords: Advertising -- Psychological aspects